HIV-1 subtype diversity, transmitted drug resistance and phylogenetics in Australia. (11th July 2018) - Pinto, Angie N; Hawke, Karen; Castley, Allison; Chibo, Doris; Giallonardo, Francesca Di; Cooper, Craig; Sawleshwarkar, Shailendra; Kelleher, Anthony; Dwyer, Dominic E
Australia has maintained a low prevalence of HIV, with a mainly concentrated epidemic and successful public health response. With the widespread availability of HIV genotyping for resistance testing, and development of phylogenetic methodologies, the field of molecular epidemiology has evolved a deeper understanding of diversity and transmission dynamics of HIV. Studies combining HIV genotype with epidemiological data have allowed insights to be gained into the changing subtype diversity, rates of transmitted drug resistance and transmission networks of HIV in Australia. This review provides an overview of HIV molecular epidemiology studies in Australia.